How far is the Global Education Reform Model globally effective ? A comparison of the relationships between student attainment and school accountability, autonomy and institutional diversity within and across national educational systems. - Gill, C (2020)
The Global Education Reform Movement (GERM) originated in the UK and US four decades ago and its prescriptions are now advanced by international development organisations as the means to raise student attainment across the world. GERM is associated with the promotion of external school accountability through the publication of assessment results, school autonomy, and school diversity to increase parental choice and bolster school independence. Aspects of GERM have been widely adopted across many member countries of the OECD and research in these countries has reported some modest gains in student attainment, but overall findings have been ambivalent. Research investigating the effectiveness of GERM in developing countries has mostly focused on single aspects of the model, such as autonomy, yet has also reported inconclusive and contradictory findings. The present study aimed to address some of the limitations of previous research by making transnational comparisons of the effectiveness of GERM using a balanced sample of non-OECD countries from the 2015 PISA cycle, which were drawn equally from four global regions and from different levels of development, and all of which had implemented GERM related reforms; within this sample the effectiveness of GERM was also investigated at an individual country level in Trinidad & Tobago, the Former Yugoslav Republic of Macedonia and Indonesia. Multilevel modelling was used to explore the associations between external accountability, school autonomy and school diversity and student maths attainment, alongside the variables of accountability to parents, internal accountability (school tracking by regulators), educational material shortages, teacher certification and principals’ leadership effectiveness which have also been proposed as factors relevant to student attainment. The main findings suggested that external accountability was modestly associated with higher levels of student attainment in high and middle income countries, but not in the least developed countries.